To simplify the expression \( 6(0.2a - 0.8b) + 4b - 8(-0.1b + 0.6a) \), follow these steps:
-
Distribute the 6 and the -8: \[ 6(0.2a - 0.8b) = 1.2a - 4.8b \] \[ -8(-0.1b + 0.6a) = 0.8b - 4.8a \]
-
Combine all the terms in the expression: \[ 1.2a - 4.8b + 4b + 0.8b - 4.8a \]
-
Group the \( a \) terms and the \( b \) terms:
- For the \( a \) terms: \( 1.2a - 4.8a = -3.6a \)
- For the \( b \) terms: \( -4.8b + 4b + 0.8b = -0.0b = 0 \)
-
So, the simplified expression is: \[ -3.6a \]
Thus, the final answer is: \[ -3.6a \]